The Use of the Bits and Pieces Game on Students’ Achievement on Writing Report Text - Ramanda Rizky; Yetty Zainil (STAI Hubbulwathan Duri, 2021)
This experimental research intended to examine the effects of the Bits and Pieces game on students’ achievement in the writing report text. Sixty-eight students in the tenth grade participated in an experimental class taught through the Bits and pieces game. The participants in the control class taught through the Conventional teaching method. After the treatment was done, the students in both grades were tested. As the results, the mean average showed that there was an increase in writing scores. Additionally, the score in the experimental class showed that the Bits and Pieces game was adequate to be taught. Nevertheless, the score in the control class showed that the Conventional teaching method was not effective to be taught because there was no significant difference between the score in the pre-test and post-test. Furthermore, learning through the Bits and Pieces game encourages students’ broader skills of cooperation and negotiation.